2005
DOI: 10.1051/0004-6361:200500175
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic collimation of the relativistic jet in M 87

Abstract: We apply a two-zone MHD model to the jet of M 87. The model consists of an inner relativistic outflow, which is surrounded by a nonrelativistic outer disk-wind. The outer disk-wind collimates very well through magnetic self-collimation and confines the inner relativistic jet into a narrow region around the rotation axis. Further, we show by example, that such models reproduce very accurately the observed opening angle of the M 87 jet over a large range from the kiloparsec scale down to the sub-parsec scale.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 34 publications
3
35
0
Order By: Relevance
“…Gracia et al 8 used the shape of the fieldline separating the two region on the boundary surface to define the opening angle. As shown in this work, this particular fieldline and flux contours of synthetic maps are parallel for a wide range of models and distances along the jet.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Gracia et al 8 used the shape of the fieldline separating the two region on the boundary surface to define the opening angle. As shown in this work, this particular fieldline and flux contours of synthetic maps are parallel for a wide range of models and distances along the jet.…”
Section: Discussionmentioning
confidence: 99%
“…Gracia et al 8 used the shape of the separating fieldline Ψ α to fit the observed opening angle as a function of distance from the core as collected by Ref. 1.…”
Section: Mhd Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The collimation of a central relativistic outflow can be provided by a non-relativistic MHD wind/jet produced by an accretion disk. Such a double jet structure was originally proposed by Sol et al (1989), and was investigated further by , Gracia et al (2005), and Beskin & Nokhrina (2006). The quasar systems with such efficiently collimated jets can be rare indeed due to the difficulties in developing the required large-scale poloidal magnetic fields in the geometrically thin accretion disks.…”
Section: The Spin Paradigmmentioning
confidence: 93%